Automation of eWeLink Based Fresh Bread Dough System - Muhammad Sofyan; Dwi Hadidjaja Rasjid Saputra (Procedia of Engineering and Life Science, 2021)
The process of plain bread dough without sugar after the fermentation process is then left to stand for a certain time manually or modern. The process of developing plain bread dough without sugar can be done by using yeast which is widely sold in the market. The yeast is mixed evenly into the dough, then covered with a cloth and left for a certain time until the dough of plain bread without sugar expands. The factors that influence the development of unsweetened bread dough are the right amount of yeast, temperature and humidity also determine the development process of the bread dough without sugar. If the supporting factors are not suitable, it can cause the plain bread dough without sugar to fail to expand. By using the automation system for bread dough without sugar based on ewelink, it can reduce the failure rate during the development process of bread dough without sugar with optimal results.